2008
DOI: 10.1128/aac.00447-08
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Staphylococcal Cassette Chromosome mec -Associated DNA Segments in Multiresistant Methicillin-Susceptible Staphylococcus aureus (MSSA) and Identification of Staphylococcus epidermidis ccrAB4 in both Methicillin-Resistant S. aureus and MSSA

Abstract: Methicillin-susceptible Staphylococcus aureus (MSSA) can arise from methicillin-resistant S. aureus (MRSA) following partial or complete excision of staphylococcal cassette chromosome mec (SCCmec). This study investigated whether multiresistant MSSA isolates from Irish hospitals, where MRSA has been endemic for decades, harbor SCCmec DNA. Twenty-five multiresistant MSSA isolates recovered between 2002 and 2006 were tested for SCCmec DNA by PCR and were genotyped by multilocus sequence typing and spa typing. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 66 publications
2
67
0
Order By: Relevance
“…within mecI [11,12]. It was also negative in a S. vitulinus strain, which was mecR1-negative by array hybridisation.…”
Section: A C C E P T E Dmentioning
confidence: 91%
See 2 more Smart Citations
“…within mecI [11,12]. It was also negative in a S. vitulinus strain, which was mecR1-negative by array hybridisation.…”
Section: A C C E P T E Dmentioning
confidence: 91%
“…This can be attributed to the insertion of a 1865 bp long IS1182 element and between the primers, M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 within mecI [11,12]. It was also negative in a S. vitulinus strain, which was mecR1-negative by array hybridisation.…”
Section: Ab5472361) and S Vitulinus (Ab5467801)mentioning
confidence: 97%
See 1 more Smart Citation
“…This specificity rate is low in comparison to other studies where specificity rates of 95"99% have been reported for chromogenic agars. [11][12][13] However, these other studies confined investigations to clinical specimens only, whereas the current study included a diverse collection of MSSA strains. The recovery of these MSSA strains as presumptive MRSA isolates has implications for the diagnostic laboratory in terms of increasing the turnaround time and resource management.…”
Section: ! )!mentioning
confidence: 99%
“…[11][12][13] However, a challenge arose for the MRSA Select II and MRSA Brilliance 2 media: each failed to detect a small number of MRSA isolates (one and three isolates, respectively) exhibiting susceptible oxacillin MICs. A small increase in the prevalence of oxacillin-susceptible mecA-positive isolates has been previously reported elsewhere and similar isolates have been recovered in the National MRSA Reference…”
Section: Limits Of Detection Assaymentioning
confidence: 99%